Adrenal response in very low birthweight babies after dexamethasone treatment for bronchopulmonary dysplasia. Issue 12 (December 1989) - Ng, P C; Blackburn, M E; Brownlee, K G; Buckler, J M; Dear, P R
Abstract : The tetracosactrin stimulation test was used to assess the adrenal responsiveness of 22 very low birthweight babies who had received a three week course of dexamethasone for the treatment of bronchopulmonary dysplasia. Five babies were studied in detail with blood samples taken for cortisol concentrations at 30 minute intervals for four hours. The tests were performed before, during, and after treatment with dexamethasone. A distinctive pattern of cortisol response to tetracosactrin was found among these babies, which was quite unlike that found in older children and adults. Using our pretreatment results as control data we conclude that there is undoubtedly evidence of modest suppression of the adrenal axis during dexamethasone treatment, although there is considerable recovery one month after stopping steroids. Basal cortisol concentrations, however, remained low in some cases, which may indicate the need for temporary corticosteroid replacement during severe illness.